Boshlang‘ich sinflarda didaktik jarayonda bolaning rivojlanishini ta’minlovchi texnologiyalar sharhi - Jumabaeva, M.P (SCIENCE and SOCIETY, 2025)
In this article, humanity, as a result of knowledge, skills, and social processes, based on state educational standards, paying attention to working with children with difficult upbringing in primary education and feeling great responsibility in the field of upbringing, the main goal of our research is to comprehensively involve children with difficult upbringing in creative activities in primary education, to help them reveal their hidden and unique abilities, to further increase their interests, to encourage and support them.
Keywords: family and school cooperation; harmony in education and upbringing; collective upbringing; important el- ements in upbringing; methods of pedagogical-psychological and moral upbringing; laws and rules of upbringing; goals and objectives of upbringing